2016
DOI: 10.5430/rwe.v7n1p52
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between CO2 Emission, Energy Consumption, Urbanization and Trade Openness for Selected CEECs

Abstract: This paper investigates the relationship between CO 2 emission, real GDP, energy consumption, urbanization and trade openness for 10 for selected Central and Eastern European Countries (CEECs), including, Albania, Bulgaria, Croatia, Czech Republic, Macedonia, Hungary, Poland, Romania, Slovak Republic and Slovenia for the period of 1991-2011. The results show that the environmental Kuznets curve (EKC) hypothesis holds for these countries. The fully modified ordinary least squares (FMOLS) results reveal that a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 21 publications
6
26
0
2
Order By: Relevance
“…The estimated coefficient of foreign trade is -0.1042 and is significant at 1% level, showing that an increase of 1% in foreign trade will result in a reduction of about 0.10% in CO 2 emissions. The finding is consistent with Destek et al [57], who concluded that a 1% increase in trade will reduce CO 2 emissions by 0.069%-0.097% in a panel of ten selected Central and Eastern European Countries (CEECs). However, OLS estimation results only reveal the influences of FDI and foreign trade in the center of the distribution of CO 2 emissions, which may cause a loss of important information in the tail distribution.…”
Section: Direct Effect Estimations Based On Panel Quantile Regressionsupporting
confidence: 90%
“…The estimated coefficient of foreign trade is -0.1042 and is significant at 1% level, showing that an increase of 1% in foreign trade will result in a reduction of about 0.10% in CO 2 emissions. The finding is consistent with Destek et al [57], who concluded that a 1% increase in trade will reduce CO 2 emissions by 0.069%-0.097% in a panel of ten selected Central and Eastern European Countries (CEECs). However, OLS estimation results only reveal the influences of FDI and foreign trade in the center of the distribution of CO 2 emissions, which may cause a loss of important information in the tail distribution.…”
Section: Direct Effect Estimations Based On Panel Quantile Regressionsupporting
confidence: 90%
“…According to this approach, a change independent variable is regressed on the independent variables using different form and optimal lag lengths. Following Siddique and Majeed (2015); Destek et al (2016) the VECM is expressed in the equations below:…”
Section: Granger Causality Testmentioning
confidence: 99%
“…They find that urbanization increases electric power consumption and carbon emission. Hassan and Salim (2015), Shahbaz et al (2015), Al-Mulali et al (2016), Ali et al (2016), Destek et al (2016), Kang et al (2016), Wang et al (2016a, b), He et al (2017) and several other studies extend the urbanization-emissions nexus to include diverse aspects. They have used multivariate frameworks to consider dimensions such as spatial dispersion, dynamics of nations, income inequality, and land use patterns, but the results were inconclusive.…”
Section: Urbanization and Co 2 Emissionsmentioning
confidence: 99%